Association of Statin Use With Kidney Damage and Function Among HIV-Infected Men. (1st October 2019) - Ascher, Simon B.; Scherzer, Rebecca; Nishtala, Arvind; Jotwani, Vasantha; Grunfeld, Carl; Parikh, Chirag R.; Ng, Derek; Wang, Ruibin; Palella, Frank J.; Shlipak, Michael G.; Estrella, Michelle M.
Abstract : Background: Chronic kidney disease (CKD) occurs commonly among HIV-infected persons. Statins may delay CKD onset and progression through their cholesterol-lowering and pleiotropic effects. Methods: Among 850 HIV-infected men from the Multicenter AIDS Cohort Study with stored urine samples (2009–2011), we evaluated cross-sectional associations of statin use with urine biomarkers of kidney damage [albumin-to-creatinine ratio (ACR), alpha-1-microglobulin, interleukin-18, kidney injury molecule-1, and procollagen type III N-terminal propeptide] using multivariable linear regression. We evaluated the longitudinal associations of statin use with annual change in estimated glomerular filtration rate by creatinine (eGFR) using linear mixed models, and with incident proteinuria and incident CKD (eGFR <60 mL/min/1.73 m 2 ) using Cox proportional hazards regression. We used inverse probability weighting to address potential confounding related to statin use. Results: Statin users comprised 30% of participants. In adjusted analyses, each year of cumulative statin use was associated with 4.0% higher baseline ACR levels ( P = 0.05), but there was no association with baseline levels of other urine biomarkers. Statin use had no overall association with annual eGFR decline. Among participants with baseline proteinuria, statin use was modestly associated with slower annual eGFR decline compared to non-use (adjusted difference: 1.33 mL/min/1.73 m 2 per year; 95% confidence interval: −0.07 to 2.70). Statin use was not associated with risk of incident proteinuria or incident CKD. Conclusions: Statin use was associated with higher baseline ACR, but not with biomarkers of tubulointerstitial injury. Statin use was associated with modestly slower eGFR decline only among participants with baseline proteinuria. Although these findings may be susceptible to confounding by indication, they suggest a limited effect of statins on CKD risk among HIV-infected men. Abstract : Supplemental Digital Content is Available in the Text.